A fully polynomial approximation scheme for a scheduling problem with intree-type precedence delays - Schuurman, Petra (Operations research letters, 1998)
We investigate a single-machine scheduling problem with precedence delays that have a simple structure: the corresponding tree has k leaves and only k+2 nodes. The objective is to minimize the makespan. We present a pseudo-polynomial algorithm for this problem, and we also give a fully polynomial approximation scheme.